Holographic imaging of unlabelled sperm cells for semen analysis: a review. Issue 10 (9th December 2014) - Di Caprio, Giuseppe; Ferrara, Maria Antonietta; Miccio, Lisa; Merola, Francesco; Memmolo, Pasquale; Ferraro, Pietro; Coppola, Giuseppe
<x xml:space="preserve">Abstract</x> Male reproductive health in both humans and animals is an important research field in biological study. In order to characterize the morphology, the motility and the concentration of the sperm cells, which are the most important parameters to feature them, digital holography demonstrated to be an attractive technique. Indeed, it is a label‐free, non‐invasive and high‐resolution method that enables the characterization of live specimen. The review is intended both for summarizing the state‐of‐art on the semen analysis and recent achievement obtained by means of digital holography and for exploring new possible applications of digital holography in this field. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> Quantitative phase maps of living swimming spermatozoa. </boxed-text>